Evaluation of elite soybean varieties for suitability in contingent summer seed production (Bangladesh Journal of Botany, 2025)
To assess the soybean varieties for suitability to seed production during the summer season, the experiment comprising seven elite varieties was laid out in R.B.D. design. The varieties MAUS 612 and MACS 1460 were promising in growth and yield attributes. The seed yield was significantly high in MAUS 612 (1863 kg/ha). The yield reduction over the average yield in Kharif was less in MAUS 612 (39.90%), MACS 1520 (40.44%) and MACS 1460 (41.20%) compared to the remaining varieties, showed their yield stability in changed growing season. MACS 1460 (19.57 kg/day/ha) and MAUS 612 (19.17 kg/day/ha) showed high GPE, while MAUS 612 (0.86) and MACS 1460 (0.80) were most promising in SYI and were found remunerative over others. Studies have shown a positive correlation between physiological traits and yield. Similarly, these two varieties were promising in terms of the quality of seed produced. Hence, MAUS 612 and MACS 1460 were suitable for contingent seed production in the summer.Bangladesh J. Bot. 54(3): 519-524, 2025 (September)